Nigel Spivey, Simon Stoddart. Etruscan Italy, an Archaeological History, London, B. T. Batsford, 1990, 168 Pp., 100 ilustr. (ISBN 0-7134-6521-2) - Martínez-pinna, Jorge (Gerión. Revista de Historia Antigua, 1991)
Sin resumen